2005
DOI: 10.1530/rep.1.00667
|View full text |Cite
|
Sign up to set email alerts
|

The genetic heterozygosity and fitness of tetraploid embryos and embryonic stem cells are crucial parameters influencing survival of mice derived from embryonic stem cells by tetraploid embryo aggregation

Abstract: The aim of this paper was to determine whether the genetic background of tetraploid embryos contributed to the survival of mice derived from embryonic stem (ES) cells by tetraploid embryo complementation. Twenty-five newborns were produced by aggregation of hybrid ES cells and tetraploid embryos with different genetic backgrounds. These newborns were entirely derived from ES cells judged by microsatellite DNA (A specific sequence of DNA bases or nucleotides that contains mono, di, tri or tetra repeats) and coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…Over the years, several studies have reported that chromosome make-up correlates with the capacity of ES cell clones to contribute to the formation of all tissues, including the germline, of the adult chimaeras. The data support the notion that karyological instability, and not loss of pluripotency, is the major reason for the lack of contribution to chimaeras of individual ES cell clones, and that karyotype analysis is a predictor of the germline transmission capacity of ES cell lines [30][31][32][33][34] . Some studies suggest that the long-term culture of iPS cells, similar to the situation for ES cells, has to be monitored carefully for culture-induced chromosomal abnormalities [35] .…”
Section: Chromosomal Abnormalitiessupporting
confidence: 71%
“…Over the years, several studies have reported that chromosome make-up correlates with the capacity of ES cell clones to contribute to the formation of all tissues, including the germline, of the adult chimaeras. The data support the notion that karyological instability, and not loss of pluripotency, is the major reason for the lack of contribution to chimaeras of individual ES cell clones, and that karyotype analysis is a predictor of the germline transmission capacity of ES cell lines [30][31][32][33][34] . Some studies suggest that the long-term culture of iPS cells, similar to the situation for ES cells, has to be monitored carefully for culture-induced chromosomal abnormalities [35] .…”
Section: Chromosomal Abnormalitiessupporting
confidence: 71%
“…For example, outbred and hybrid tetraploid host embryos were found to be superior to inbred strain tetraploid host embryo tested with the same F1-hybrid ES cell line. 28 Apart from increased body weight, ES cell derived animals were shown to be phenotypically normal and not different from isogenic controls from normal mating. 57 This ability to derive embryos and mice directly from ES cells represents a unique method to study gene families and pathways and for rapid phenotype analysis.…”
Section: • Diploid-tetraploid Embryos • Es Cells-tetraploid Embryosmentioning
confidence: 99%
“…22,[26][27][28] This ability of tetraploid cells to persist in the embryo proper has important implications for experimental interpretation and is the basis for the recommendation that reporters such as EGFP or lacZ be used to distinguish cells originating the tetraploid host embryos from those derived from ES cells at later stages of gestation. 29,30 There are two main types of chimeras that can be generated with tetraploid embryos:…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For the MA ES cell line series, we used outbred mice that were produced by crossing the 129 and BALB lines (hereafter, referred to as 1B), for the MC series-F 1 (1B 9 C57BL), and for MD-F 1 (1B 9 DD). We derived ES cells from hybrid embryos because such ES cells have higher chimerization efficiency compared to a linear genetic background (Eggan et al 2001(Eggan et al , 2002Li et al 2005).…”
Section: Es Cell Derivation and Culturementioning
confidence: 99%